The Impact of Pharmaceutical Care Implementation on The Incidence of Drug-Related Problem and Clinical Outcome of Hypertension Patients at Puskesmas Lubuk Pakam in 2021 - Darmirani, Yosi; Dalimunthe, Aminah; Khairunnisa; Iksen (Fakultas Farmasi, Universitas Surabaya, 2023)
The role of pharmacists in the implementation of pharmaceutical care has been shown to improve the outcome of therapy in hypertension patients in various countries. This study aimed to implement pharmaceutical care for hypertension patients and determine its impact on the incidence of drug-related problems (DRPs) and clinical outcomes of hypertension patients in Puskesmas Lubuk Pakam. This study used a comparative experimental method before and after the intervention of 73 hypertension patients in March-August 2021. Identification of the of DRPs was using the PCNE V9.00 standard and blood pressure values were obtained from direct examination of patients. Data were analyzed using the Wilcoxon Signed-Rank test. The results showed that the average DRPs incidence was significantly reduced after the intervention (observation, interview, and education) on the hypertension patients. The average blood pressure before intervention was 154.38 ± 16.20 mmHg and after intervention became 144.04 ± 15.94 mmHg (p value = 0.000). Based on the results of the study, it can be concluded that the application of pharmaceutical care can reduce the incidence of DRPs and improve clinical outcomes in hypertension patients in Puskesmas Lubuk Pakam.